Control strategies for Conyza spp. in soybean pre-planting: Single or sequential applications? (Research, Society and Development, 2021)
Conyza spp. it is a difficult species to control, especially in more advanced phenological stages requiring specific chemical control strategies. The objective of this work was to evaluate the control of Conyza spp. through an application of 2,4-D herbicide + glyphosate, followed or not, by sequential applications of desiccant herbicides in isolation and/or associated with pre-emergent herbicides in pre-planting of soybean crop. The experiment was carried out in the field in an area with natural infestation of Conyza spp. in a randomized block experimental design with 4 replications and 18 treatments. An application of 2,4-D + glyphosate (975 + 1025 g a.i. ha-1) was performed and 15 days after the initial application (DAI) sequential applications were performed: diquat (400 g a.i. ha-1); carfentrazone (30 g a.i. ha-1); glufosinate ammonium (500 g a.i. ha-1); saflufenacil (49 g a.i. ha-1) individually and associated with flumioxazim + imazethapyr (50 + 100 g a.i. ha-1); sulfentrazone + diuron (245 + 490 g a.i. ha-1) and diclosulam (29.4 g a.i. ha-1) and the control without herbicide application. A single 2,4-D + glyphosate application was not effective in the control. Applications that relied on carfentrazone were ineffective in controlling. Diquat, saflufenacil and ammonium glufosinate, associated with pre-emergent herbicides (diclosulam, sulfentrazone + diuron and flumioxazim + imazethapyr), resulted in a control greater than 80%. Carfentrazone is not an alternative for the control of Conyza spp., diquat, glufosinate ammonium and saflufenacil isolated and/or associated with pre-emergent herbicides are viable in the control of Conyza spp.